DILEMA KONSEP SASTRA - Wargadinata, Wildana (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2007)
Many people admit that the discussion of literary concept has never reached the final agrement. That is why literature is considered to be peculiar and particular as well. The literary concept increasingly becomes a dilemma when the concept is supposed to be included in a separate specific area, that is, Islamic literary concept. According to the writer, the dilemma of literary concept constitutes a potential substance especially for developing literature paradigm ahead.